Aktivitas Petani Sayur di Nagari Padang Laweh Dalam Seni Grafis - Ahmad Jamil Illahi; Irwan Irwan (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2025)
This research aims to visualize the activities of vegetable farmers in Nagari Padang Laweh in graphic art, this explains the daily activities of vegetable farmers which have become a community habit and become the livelihood of the people in the author's environment, therefore the author raises the work with the title Activities of vegetable farmers in Nagari Padang Laweh in graphic art and a form of depiction of people's daily lives in planting vegetables and other activities in the fields starting from the beginning of the planting process through several processes until harvesting the field results. The creation method used is the art consortium method through five stages of work, namely: (1) preparation, including observation and exploration: (2) elaboration, including collecting references: (3) synthetic, namely the application of the main idea: (4) realization of the concept through creation work: and (5) the completion stage in the form of preparing a report and exhibition of the final work. The results of this research are ten works of graphic art measuring 50cm x 60 cm, the works of which are entitled: Clearing Land, Planting, Transporting Fertilizer, Fertilizing, Regret in the Midst of Harvest, Toiling in the Fields, Making a Living, Farmer's Life, Generation of Farmers, Human Harmony and Natural,